Quality detection and performance optimization of antenna system for 2G/3G and 4G - Wentao ZHU; Feng GAO; Kai HE; Zhiyuan SONG (Dianxin kexue)
The urgent monitoring and diagnosing problem of antenna system was researched.Firstly,problems and fault diagnosis situation of antenna were analyzed.Secondly,by analyzing the impact of the antenna system parameters on network quality,a platform of antenna quality detection and fault diagnosis for GSM,TD-SCDMA and TD - LTE network was developed.Finally,the practicality and accuracy of research results is verified through the web application.With this method,the parameters of the antenna and cable system could be detailedly analyzed.it broken away from the traditional fix- after- failure maintenance process by finding small problems which was hard to identify before major failures occur.